Influence of film thickness on structural, optical, and electrical properties of sputtered nickel oxide thin films - Rezaee, Sahar; Korpi, Alireza Grayeli; Karimi, Maryam; Jurečka, Stanislav; Arman, Ali; Luna, Carlos; Ţălu, Ştefan (Microscopy research and technique, 2024)
Utilizing radio frequency magnetron sputtering, we successfully fabricated nickel oxide thin films with different thickness (from 80 to 270 nm), and conducted an in‐depth examination of their structural, morphological, optical, and electrical properties. The crystal structure and surface roughness were determined using x‐ray diffraction (XRD) and atomic force microscopy (AFM), respectively. The XRD analyses showed that the films were composed of cubic nickel oxide, exhibiting a notable orientation along the (200) direction. This crystal texture partially increased when the film thickness reached 270 nm. In addition, a direct correlation between film thickness and crystallite size was observed, with the latter increasing as the former did. AFM analysis provided insights into the surface morphology, revealing metrics like the bearing area, 3D surfaces intersections, and statistical properties of surface height. These insights underscore the relationship between film thickness and surface properties, which in turn influence the overall electrical, and prominently, optical properties of the films. Employing transmittance UV–visible spectroscopy, we characterized the optical behavior of these films, noting a proportional increase in refractive index with film thickness. Additionally, resistivity was observed to increase concomitantly with film thickness. In conclusion, the deposition process's film thickness acts as a pivotal parameter for fine‐tuning the structural, morphological, and optical properties of nickel oxide thin films. This knowledge paves the way for optimizing nickel oxide‐based devices across various applications. Research Highlights We synthesized and characterized of p‐type semiconducting NiO thin films sputtered on substrates by using RF magnetron sputtering with different thickness. Advanced crystalline structures and fractal features extracted from XRD and AFM analysis. The 2D and 3D surface analysis of the samples indicates a complex structure with an imperfect self‐similarity that suggests a multifractal structure. We represented graphically the relative representation of higher geometric objects in the AFM image. We attributed the optical and electrical properties of the samples to the crystallite size, and the concurrent reduction in oxygen vacancies and crystalline defects within the films. Illustrative representation of the magnetron sputtering system. The multifractal analysis for NiO thin films with different thicknesses. UV–visible transmittance spectra for the four studied samples.